Analysis of Risk Factors of Oral Cancer and Periodontitis from a Sex- and Gender-Related Perspective: Gender Dentistry - Federica Di Spirito; Alessandra Amato; Antonio Romano; Gianna Dipalma; Edit Xhajanka; Adone Baroni; Rosario Serpico; Francesco Inchingolo; Maria Contaldo (Applied Sciences, 2022)
Gender-specific medicine studies how sexual biology and gender-related cultural and behavioral differences may influence a person’s health and considers the differences in clinical features, prevention, therapies, prognosis, and psycho-social aspects of diseases with different impacts on women and men. The present work summarizes the main differential impact each risk factor for oral cancer and periodontitis has according to biological sex- and gender-oriented differences. It resulted in differences in epidemiology and the weight of various healthy determinants that may influence the incidence and prognosis of oral cancer and periodontitis. It is desirable to change the methodology of scientific studies with a higher focus on the weight that sexual variables may have on the well-being or the probability of getting ill of each person, thus promoting the development and diffusion of personalized gender dentistry.